Doctoral theses on Laestadius and the Laestadian movement 1937–2018 - Andreassen, Bengt-Ove (Approaching religion, 2020)
The scope of the review is all doctoral theses that exist on Laestadius and the Laestadian movement. A total of 31 doctoral theses on Laestadius and the Laestadian movment are included in this review.The Laestadian movement is an international one, albeit primarily established in the Nordic countries, Finland, Norway and Sweden. The review aims at presenting an overview of doctoral theses, countries which they are produced, which academic disciplines that have contributed in this research, and finally discuss some main tendencies.